Optimization of anodic porous transport electrodes for proton exchange membrane water electrolyzers. Issue 47 (20th November 2019) - Bühler, Melanie; Hegge, Friedemann; Holzapfel, Peter; Bierling, Markus; Suermann, Michel; Vierrath, Severin; Thiele, Simon
Abstract : In this study we optimize anodic porous transport electrodes (PTEs) for proton exchange membrane water electrolysis (PEMWE) in terms of the titanium substrate, IrO2 catalyst loading and Nafion content. Abstract : In this study we investigate the potential of porous transport electrode (PTE) based membrane electrode assemblies (MEAs) for proton exchange membrane water electrolysis. The focus is on the overpotential determining anodic PTE for the oxygen evolution reaction. The influences of catalyst loading, ionomer content and porous titanium substrate on the polarization behavior are analyzed. The comparison of a porous fiber-sintered substrate with a powder-sintered substrate shows no significant differences in the kinetic and mass transport regions. Ohmic losses, however, are lower for fiber PTEs above a catalyst loading of 1.0 mgIrO2 cm −2 . Variations of the Nafion content in the catalyst layer reveal changes of mass transport and ohmic losses and have an influence on the reproducibility. Varying the noble metal loading and therefore the thickness of the applied catalyst layer influences the kinetic region and ohmic resistance of the MEAs. The best compromise between reproducibility and performance is found for a loading of 1.4 mgIrO2 cm −2 and 9 wt% Nafion. The stable operation of the aforementioned PTE is shown in a 200 h durability test at 2 A cm −2 .